Roman philosophy and the good life - Belliotti, Raymond A., 1948- (Lexington Books, 2009)
Raymond Angelo Belliotti's Roman Philosophy and the Good Life provides an accessible picture of these major philosophical influences in Rome and details the crucial role they played during times of major social upheaval. Belliotti demonstrates the contemporary relevance of some of the philosophical issues faced by the Romans, and offers ways in which today's society can learn from the Romans in our attempt to create meaningful lives.